Pigmented Kamino bodies: a little-known histological finding. Prevalence in 19 cases of Reed nevus - Ana Caroline Barreto Antunes; Aline Caixeta Guimarães Véspoli; Paula Silva Ferreira; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2017)
Abstract The present study aimed to determine the prevalence of Kamino bodies in Reed nevus, since most studies to date show conflicting data on this issue. This was a retrospective observational study, in which the histopathology of 19 Reed nevus lesions were reviewed. The slides were stained by hematoxylin and eosin and periodic acid-Schiff, with a special focus placed on the identification of Kamino bodies. Some clinical data were also collected. The median patient age was 12 years (range of 2 to 58). The women to men ratio was 5:4. Lesions were located on different parts of the body. Kamino bodies were found in eleven lesions (57.89%). five showed pigmented Kamino bodies (26.31%), four non-pigmented Kamino bodies (21,05%), and 2 (10.52%) had both. Kamino bodies, pigmented or not, are a common histological finding in Reed nevus and may well represent a good marker to differentiate these from malignant melanomas.